2019
DOI: 10.1093/cid/ciz860
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prophylactic Anti–Hepatitis B Virus Therapy With Improved Long-term Survival in Patients With Hepatocellular Carcinoma Undergoing Transarterial Therapy

Abstract: Background The effect of prophylactic antiviral therapy (AVT) on survival of patients with hepatitis B virus (HBV)–related hepatocellular carcinoma (HCC) remains unknown. This study aimed to determine whether prophylactic AVT could improve long-term survival in patients undergoing transarterial chemotherapy (TAC). Methods Between 2002 and 2016, 2860 newly diagnosed HBV-related patients with HCC treated with TAC were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
1
26
0
2
Order By: Relevance
“…In the current study, we found that nearly 60% HBV-HCC patients with a high viral load pre-TACE achieved VR after NA therapy. Moreover, our findings suggest that NA therapy with achievement of VR improves OS after TACE for HBV-HCC, which is consistent with a recent study reported by Jang and colleagues (18).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, we found that nearly 60% HBV-HCC patients with a high viral load pre-TACE achieved VR after NA therapy. Moreover, our findings suggest that NA therapy with achievement of VR improves OS after TACE for HBV-HCC, which is consistent with a recent study reported by Jang and colleagues (18).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, HCC patients undergoing TACE can benefit from NA therapy as reported in the previous studies (16,17). Recently, a large-scale study has revealed that prophylactic antiviral therapy is associated with better long-term survival among HBV-HCC patients undergoing TACE (18).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Several studies have reported that antiviral therapy including TACE and RFA is minimally invasive, can improve the survival rate, and reduce the recurrence rate after resection. [4][5][6][7][8][9][10][11][12][13][14] Therefore, it is recommended that HBVassociated HCC patients, particularly those with high viral loads, receive antiviral therapy. A retrospective cohort study recently revealed that 19.9% of chronic hepatitis B(CHB) patients had low-level viremia (LLV; 20-2000 IU/mL) after entecavir (ETV) treatment.…”
Section: Introductionmentioning
confidence: 99%